2010
DOI: 10.1007/s10439-010-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Flow Residence Time and Regions of Intraluminal Thrombus Deposition in Intracranial Aneurysms

Abstract: Abstract-Thrombus formation in intracranial aneurysms, while sometimes stabilizing lesion growth, can present additional risk of thrombo-embolism. The role of hemodynamics in the progression of aneurysmal disease can be elucidated by patient-specific computational modeling. In our previous work, patient-specific computational fluid dynamics (CFD) models were constructed from MRI data for three patients who had fusiform basilar aneurysms that were thrombus-free and then proceeded to develop intraluminal thrombu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 25 publications
1
173
0
1
Order By: Relevance
“…These observations are physically similar to the separation of the boundary-layer downstream of stenoses, where Raz et al [30] showed the direct relationship between platelet recirculation time and both platelet activation and acetylated thrombin generation. Furthermore, Rayz et al [31] observed thrombus deposition in certain regions of patient-specific intracranial geometries with an increase in residence time and low WSS. More recently, Boyd et al found that AAA rupture tended to occur in thrombus afflicted regions with predicted flow recirculation and low WSS [32].…”
Section: Introductionmentioning
confidence: 99%
“…These observations are physically similar to the separation of the boundary-layer downstream of stenoses, where Raz et al [30] showed the direct relationship between platelet recirculation time and both platelet activation and acetylated thrombin generation. Furthermore, Rayz et al [31] observed thrombus deposition in certain regions of patient-specific intracranial geometries with an increase in residence time and low WSS. More recently, Boyd et al found that AAA rupture tended to occur in thrombus afflicted regions with predicted flow recirculation and low WSS [32].…”
Section: Introductionmentioning
confidence: 99%
“…To track contrast agent, Rayz et al solved an advection equation with a zero source term. 19 Narracott et al calculated RT to model clot formation in a stenosis using an advection-diffusion equation with a non-zero source term. 20 In that study, a non-zero source term was used for the entire computational domain and dye was advected from the inlet, so the value of RT depended on the distance from the model inlet to the region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the WSS or WSR may be responsible for the remodeling of the vascular endothelium, and WSR has been correlated with the location of vascular thrombus in the previous study (36). The WSR clearly indicates the strength of near-wall flow relative to the wall, since it is defined by the flow velocity gradient at the wall.…”
Section: Methodsmentioning
confidence: 68%